Impact of MRI/US fusion‐guided prostate biopsy on biopsy‐naïve patients: A single urologist's experience. Issue 1 (4th May 2021) - Altok, Muammer; Demirel, Cihan; Kang, Hyunseon C.; Choi, Haesun; John, David; Inguillo, Irene A.; Davis, John W.; Ward, John F.
Abstract: Objectives: To report our experience with imaging‐guided targeted prostate biopsy (IGTpBx) for patients undergoing initial prostate biopsy in a clinical setting. Materials and methods: From July 2014 to February 2020, 305 men who had IGTpBx performed as their first prostate biopsy were enrolled. Two dedicated magnetic resonance imaging (MRI) radiologists segmented at least 1 region of interest (ROI) for each of these men using screening 1.5T MRI images. A single urologist employed the robotic‐assisted Artemis MRI/ultrasonography (US) fusion platform to obtain 2‐3 targeted samples from each ROI and additional random samples from the zones of the prostate outside the ROIs (a total of 12 zonal samples). Biopsy outcomes were categorized based on the Gleason score (GS) grade group (GG) as no cancer, favorable (GG < 3 or GS < 4 + 3), or clinically significant (GG ≥ 3 or GS ≥ 4 + 3) cancer. Results: The overall cancer detection rate was 75%:31% clinically significant, 44% favorable, and 25% no cancer. These findings triggered active interventions in 176 (58%) patients. A prostate‐specific antigen (PSA) level of 0–4 ng/mL was detected in 39 (66%) of 59 patients (32 favorable, 7 significant), 4–10 ng/mL in 147 (77%) of 190 patients (85 favorable, 62 significant), and 10 ng/mL and over in 44 (80%) of 55 patients (17 favorable, 27 significant). Conclusions: The tumor detection rate was 75% with IGTpBx in patients without a previous biopsy. In addition, about 42% of detected cancers were deemed clinically significant and led to active interventions. IGTpBx as a patient's first prostate biopsy improves the detection of clinically significant prostate cancer when compared with historical data for random systematic prostate biopsy.